Could forage peanut in low proportion replace N fertilizer in livestock systems? - Longhini, Vanessa Z. [UNESP]; Cardoso, Abmael S. [UNESP]; Berca, Andressa S. [UNESP]; Boddey, Robert M.; Reis, Ricardo A. [UNESP]; Dubeux, Jose C. B.; Ruggieri, Ana C. [UNESP] (Public Library Science, 2021)
Palisadegrass [Urochloa brizantha (Hochst. ex A. Rich.) R. D. Webster cv. Marandu] is widely used in Brazil and is typically managed with little or no N fertilizer, which often leads to pasture decline in the long-term. The current relationship between beef price and fertilizer cost in Brazil does not favor fertilizer use in pastures. Legume inclusion is an alternative to adding fertilizer N, but often legumes do not reach a significant proportion (> 30%) in pasture botanical composition. This study evaluated herbage responses to N inputs and pasture species composition, under intermittent stocking. Treatments included palisadegrass-forage peanut (Arachis pintoi Krapov. & W.C. Greg. cv. Amarillo) mixture (mixed), unfertilized palisadegrass (control), and palisadegrass fertilized with 150 kg N ha(-1) yr(-1) (fertilized). Treatments were applied over two rainy seasons with five growth cycle (GC) evaluations each season. Response variables included herbage biomass, herbage accumulation, morphological components, total aboveground N of forage peanut (TAGN(FP)), and contribution of biological N-2 fixation (BNF). Herbage biomass was greater for fertilized palisadegrass [5850 kg dry matter (DM) ha(-1)] than for the palisadegrass-forage peanut mixture (3940 kg DM ha(-1)), while the unfertilized palisadegrass (4400 kg DM ha(-1)) did not differ from the mixed pasture. Nitrogen fertilizer increased leaf mass of palisadegrass (2490 kg DM ha(-1)) compared with the control and mixed treatments (1700 and 1310 kg DM ha(-1), respectively). The contribution of BNF to the forage peanut ranged from 79 to 85% and 0.5 to 5.5 kg N ha(-1) cycle(-1). Overall, benefits from forage peanut were minimal because legume percentage was less than 10%, while N input in the system by N-fertilizer increased palisadegrass herbage biomass.